Case Report: Spontaneous pregnancy after fertility-preserving treatment in a patient with low-grade endometrial stromal sarcoma and literature review - Wang, Manrong; Wu, Pengfei; Wang, Lulu; Liu, Sijia; Gama, Qujia; Lv, Qiaoying; Zhang, Jinyu; Yu, Min; Wang, Yiqin; Ma, Fenghua; Shan, Weiwei; Luo, Xuezhen (Frontiers in Oncology, 2025)
IntroductionLow-grade endometrial stromal sarcoma (LGESS) is a rare malignant tumor of the uterus, characterized by slow growth. Early-stage LGESS is associated with favorable survival, but it has a high recurrence rate. The primary treatment for this disease is full-staging surgery. In this report, we present a case to explore the potential for fertility-preserving treatment in young women with LGESS.Case presentationA 29-year-old nulliparous patient diagnosed with stage IA LGESS underwent conservative treatment at the Obstetrics and Gynecology Hospital of Fudan University. After fertility-sparing surgery and three months of hormone treatment, no residual lesions were found. Subsequently, the patient conceived spontaneously and successfully delivered a healthy baby. However, she experienced recurrence eight months after delivery but declined hysterectomy and follow-up care.ConclusionsCurrently, there is still no standard management protocol for fertility preservation therapy in LGESS. Both previously reported cases and our case suggest that fertility-sparing treatment may be an option for carefully selected patients with LGESS. Further research and larger clinical studies are necessary to explore fertility-preserving treatments for young nulliparous patients with LGESS to establish guidelines or consensus.